2020
DOI: 10.3390/app10176067
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Cognitive Architecture for Social Robots: Integrating Behaviors and Symbolic Knowledge

Abstract: This paper presents the evolution of a robotic architecture intended for controlling autonomous social robots. The first instance of this architecture was originally designed according to behavior-based principles. The building blocks of this architecture were behaviors designed as a finite state machine and organized in an ethological inspired way. However, the need of managing explicit symbolic knowledge in human–robot interaction required the integration of planning capabilities into the architecture and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…By running on ROS2, PlanSys2 already has a large number of features related to security and predictability. ROSPlan is only capable of controlling one robot, and, in our experience, using it in various robotics research and competitions [26], it is not as efficient as we wished.…”
Section: Related Workmentioning
confidence: 83%
“…By running on ROS2, PlanSys2 already has a large number of features related to security and predictability. ROSPlan is only capable of controlling one robot, and, in our experience, using it in various robotics research and competitions [26], it is not as efficient as we wished.…”
Section: Related Workmentioning
confidence: 83%
“…Francis et al [12], in their survey, identified the following forms of context: cultural context [26,34,85,[215][216][217], environmental context, individuals diversity, task context, and interpersonal context, but their literature review in this area is narrow. The notion of context is usually regarded in the deliberative layer of the robot's planning and embedded as spatial or spatiotemporal constraints in the motion planning [17,218,219].…”
Section: Contextual Awarenessmentioning
confidence: 99%
“…ROS has also been used in ROSBOT [184], a low-cost robotic platform with the capacities of obstacle avoiding navigation, face detection, and other social behaviors. Moreover, ROS was used in the implementation of cognitive mechanisms to allow robots to socially interact with humans [185][186][187]. Figure 5 shows another platform, the UXA-90 humanoid robot, developed to serve several purposes with 23 degrees of freedom and supporting ROS [188].…”
Section: Operating Systems and Other Softwarementioning
confidence: 99%